(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article brings to light the importance of speaking skills. The author adopts a communicative approach for the enhancement of speaking skills of her students in the class. The researcher focuses on the processes involved in the conversational interaction of the students, thereby conducting such activities in the class which enable her students to be ‘able to use the language appropriate to given social context. The author’s consideration is that the role of the teacher is a technician or an engineer. The teacher’s task is to focus the students’ attention, and provide exercises to help them develop language facility; however, to ensure their self-reliance, the teacher should only help the students as much as is strictly necessary. All our software development today, the communication facilities available to us through internet, our access to a variety of websites, are all being carried out in English. Most of the research works are conducted and compiled in English. Anything written and recorded in this language is read and listened to, in wider circles. As a result, English is being taught and learned around the world as a second language today.